2022
DOI: 10.1021/acsaem.1c03928
|View full text |Cite
|
Sign up to set email alerts
|

Ti3C2 MXene-Reduced Graphene Oxide Composite Polymer-Based Printable Electrolyte for Quasi-Solid-State Dye-Sensitized Solar Cells

Abstract: The liquid electrolyte causes the corresponding leakage and sealing problems in the construction of dye-sensitized solar cells (DSSCs). Currently, quasi-solid-state polymer-based electrolytes have been reported to effectively improve the leakage and volatilization of traditional liquid electrolytes in DSSCs. In this work, reduced graphene oxide (rGO) and the intercalation of MXene/rGO were utilized in the copolymer polyethylene oxide/poly(vinylidene fluoride-co-hexafluoropropylene) as a printable gel electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Subramanian et al 57 developed functionalized DSSC by incorporating 1D TiO 2 into PVDF-HFP/PMMA copolymer for LiI electrolyte to achieve solar conversion efficiency of 8.08% owing to excellent entrapping of smaller electrolyte cation (Li + ) across copolymer interchain. Wen et al 58 developed 2D-functionalized copolymer (PEO/PVDF-HFP) electrolyte to serge the solar conversion efficiency of 8.26% in DSSC. 2D mixed surface (Ti 3 C 2 -rGO) enhanced electrolyte conductivity and charge transmission between the DSS photoanode and cathode.…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
“…Subramanian et al 57 developed functionalized DSSC by incorporating 1D TiO 2 into PVDF-HFP/PMMA copolymer for LiI electrolyte to achieve solar conversion efficiency of 8.08% owing to excellent entrapping of smaller electrolyte cation (Li + ) across copolymer interchain. Wen et al 58 developed 2D-functionalized copolymer (PEO/PVDF-HFP) electrolyte to serge the solar conversion efficiency of 8.26% in DSSC. 2D mixed surface (Ti 3 C 2 -rGO) enhanced electrolyte conductivity and charge transmission between the DSS photoanode and cathode.…”
Section: Functional Electrolyte Photovoltaic Reactions and Redox Pote...mentioning
confidence: 99%
“…Vapour transport deposition (VTD) was used to deposit Sb 2 Se 3 lm and its orientation in 2018 to enhance carrier transport and e ciency. The most e cient Sb 2 Se 3 nanorod arrays on a Mo electrode were created in 2019 using the CSS method [17].…”
Section: Related Work Donementioning
confidence: 99%
“…To improve the stability and sustainability of DSSCs, scientists have developed different types of quasi-solid electrolytes, new redox electric pairs , (based on metal complexes or organic compounds), or new solvents to dissolve electrolytes . Our research group reported a new type of quasi-solid electrolyte composited with SiO 2 aerogel and graphene (GR), multiwalled carbon nanotubes, or polyaniline.…”
Section: Introductionmentioning
confidence: 99%